Management of Disastrous Complications of Penile Implant Surgery. Issue 7 (1st July 2021) - Bettocchi, C.; Osmonov, D.; van Renterghem, K.; Djiovic, R.; Ralph, D.J.
ABSTRACT: Rationale: Penile Prosthesis Implantation (PPI) is the definitive treatment for Erectile Dysfunction not responsive to conservative management strategies. Furthermore, it is a staple of surgical treatment of severe Peyronie's Disease (PD) and phallic reconstruction. Expert implantologists occasionally face disastrous complications of penile implant surgery which can prove to be very challenging. In this article we present a selected number of case reports which exemplify this kind of situations and discuss management strategies while also commenting on plausible aetiologies. Patients' concerns: The first case describes a PPI performed in end-stage fibrotic corpora after multiple instances of implantation/explant. The second and third cases show two diametrically opposed approaches to the management of glans necrosis after PPI in post-radical cystectomy patients. The fourth case describes the history of a diabetic patient suffering from glandular, corporal and urethral necrosis after a complicated PPI procedure. The fifth case reports the surgical treatment of a case of recurring PD due to severe scarring and shrinking of a vascular Dacron patch applied in a previous operation. Diagnosis: Complication diagnosis in all patient was mainly clinical, intra- and postoperative, with Penile Color Doppler Ultrasonography performed when needed in order to demonstrate penile blood flow. Interventions: The patients underwent complex surgical procedures that addressed each specific complication. Complex penile implants with fibrosis-related complications, penile prosthesis explant with and without surgical debridement of necrotic areas, penile prosthesis explant with necrotic penile shaft and urethral amputation with perineostomy, and complex corporoplasty with scar tissue excision and patch application with PPI were performed in the five patients. Outcomes: Penile anatomy and erectile function with PPI was achieved in 4 out of 5 patients. 1 of 5 patient is scheduled to undergo a total phallic reconstruction procedure at the time of this writing. Lessons: Management of disastrous complications of penile implant surgery can be very challenging even in expert hands. In-and-out knowledge of possible PPI and PD complications is required to achieve an acceptable outcome.